Genetic principles of the philosophy of perfect education - Valentyn Pomohaibo; Andrii Pomohaibo (Філософія освіти, 2021)
Based on the analysis of the content of the book of famous British behavioral geneticists K. Asbury and R. Plomin «G means genes: the impact of genetics on education and achievement» shows the way to create a perfect school education, based on the latest numerous large-scale and long-term researches in different countries and prove that the role of genetic factors in human learning and life success is not absolute and that the impact of the environment is no less important than genes. This thesis is a base of the personalized child education idea. Based on an analysis of the research results, the authors of the book assert that school education should be personalized. It is the personalization of learning that will ensure to develop the thinking ability, acquire knowledge and skills at a pace and direction that is appropriate for each child. Personalized learning should be based on the following principles: a minimization of the core curriculum and test basic knowledge and skills; a maximizing of options to all pupils alongside the compulsory basic knowledge and skills; a stopping of labeling ability of children; an individual education of each pupil; a teaching of children to achieve success; a promotion of equal opportunities for children from an early age; an availability of out-of-school education for all children; a two-stage physical education program; wide choice of future life ways; a training of new teachers in genetics and a giving them the methods to put it into pedagogical practice; the scale of schools in directions and levels of education. Finally, the authors of the book offer their vision of a school that will be based on the laws of behavioral genetics. Possible publication of the book by K. Asbury and R. Plomin, «G is for genes: The impact of genetics on education and achievement» in Ukrainian will be an interesting and useful handbook for policymakers, educators and parents with its constructive recommendations on one of the most important educational challenges – how to prepare each and every child for a successful life in today's ever-changing world.